A Proposed Architectural Framework of Orthogonal Handshaking Authentication Protocol (OHSAP) for Secure Private Cloud Data Transactions on Client based Access mechanism - Sirajudeen, M.Mohamed; Siddiq, M.Abubacker (IJRDO-Journal of Applied Science, 2015)
In the emerging trends in cloud computing help to reduce the operating cost for required resources irrespective of the geographical barriers. Simultaneously, the data/information access by various clients arises too many security issues in the existing cloud deployment models. Especially, profitable oriented transactions give more attention for secure data transmission between the clients and cloud service providers (CSP). Usually, the programmers /researchers follow a method of encryption /decryption to protect the data from intruders. In this proposed approach faintly different from the existing one with some additional features for the cloud service provider’s location in order to store the encrypted data (ED) and the Encryption key. The security related protocols are usually run over the untrusted networks regarding to ensure the secure data transactions. Private Clouds play an important role to access confidential /privacy information’s for an individuals or an organization. It will be composed into two major issues: client based access mechanism and server based access mechanism. In this proposed architectural framework to describe the client based access mechanisms with all required features.